2017
DOI: 10.1051/sicotj/2017032
|View full text |Cite
|
Sign up to set email alerts
|

Longus colli tendinitis. A review of literature and case series

Abstract: Purpose: To increase the awareness of longus colli tendinitis (LCT) among spine specialists and to present a practical overview of diagnostic and treatment options, so that unnecessary interventions are avoided. Five sample cases from a German spine center will also be presented. Methods: Literature review and case series. A PubMed search was performed in May 2015, and the articles found were reviewed for clinical presentation, investigations, and treatment. The frequency of publication of LCT cases and the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 24 publications
1
34
0
1
Order By: Relevance
“…Some cases of LCT, such as our own, do not show calcification on imaging studies, although most do ( 5 ). In cases without calcification, prevertebral effusion on T2-weighted images is important for achieving a diagnosis of LCT.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Some cases of LCT, such as our own, do not show calcification on imaging studies, although most do ( 5 ). In cases without calcification, prevertebral effusion on T2-weighted images is important for achieving a diagnosis of LCT.…”
Section: Discussionmentioning
confidence: 69%
“…On imaging studies, such as CT and MRI, calcification along the longus colli is often noted. A review of the literature that included 242 cases of acute calcific vertebral tendinitis reported by 104 articles revealed that the mean age was 43 years (21-81 years), the CRP values in 21 cases ranged from 0.3 to 91.3 mg/dL (mean 23.66 mg/dL), and the ESR in 45 cases ranged from 5 to 98 mm/h (mean 31.57 mm/h) based on blood tests ( 5 ). The present case showed severe inflammation on blood tests and no calcification on imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of both prevertebral calcification and oedema on CT is considered highly characteristic for acute longus colli tendinitis, and this simultaneous finding should help to distinguish this condition from an infectious aetiology 9 14–17. Other differential diagnoses that can present similarly include retropharyngeal abscess, pharyngitis, spondylitis, vascular conditions 18 19. A retrospective study published in 2017 attempted to determine the frequency of acute longus colli tendinitis on diagnostic CT imaging performed at a large multicenter healthcare system 20.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiologic basis of the condition is a foreign-body inflammatory response to deposited calcium hydroxyapatite in the superior oblique tendon of the longus colli. In studies [ 8 ] that used CT or MRI, calcifications were obvious in 185 cases (approximately 76.44%), and in 190 (78.51%) cases, prevertebral soft-tissue swelling or effusion was present. In 14 (5.7%) cases, there was no comment on the presence of effusion or soft-tissue edema, while in 6 cases soft-tissue swelling or effusion was absent.…”
Section: Discussionmentioning
confidence: 99%
“…In the published literature, we found no mention of vertigo. Only 1 report [ 8 ] mentioned dizziness and nausea, but no case reports or analysis of vertigo symptoms were reported in the references in this study. [ 9 ] Calcifications were evident in 209 cases (76.8%) in which computer tomography (CT) or MRI were used.…”
Section: Case Reportmentioning
confidence: 97%